1986
DOI: 10.1159/000298949
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bile Acids, Gamma-Glutamyltransferase and Routine Liver Function Tests in Emetic and Nonemetic Pregnancies

Abstract: The etiology of nausea and vomiting in pregnancy is still unknown. One possibility is that ovarian and placental hormones may play some part. The liver is the major site of metabolic inactivation of steroid hormones. In this study, 102 healthy pregnant women, of whom 62 complained of nausea, were followed throughout pregnancy. Liver function tests were performed to ascertain whether emesis gravidarum is related to impaired hepatic function. In this series, all values were within the normal ranges. Serum levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Our results are in agree with Bacq et al, (1996);Järnfelt-Samsioe et al, (1986); Knopp et al, (1985) indicated that total bilirubin concentration are decreased during all three trimesters of pregnancy.…”
Section: Resultssupporting
confidence: 93%
“…Our results are in agree with Bacq et al, (1996);Järnfelt-Samsioe et al, (1986); Knopp et al, (1985) indicated that total bilirubin concentration are decreased during all three trimesters of pregnancy.…”
Section: Resultssupporting
confidence: 93%
“…The increase was insignificant (p>0.05) in the 1 st and 2 nd trimesters compared to nonpregnant women (p>0.05). This is in agreement with other studies, which have shown a slight increase in ALT and or AST in the third trimester of pregnancy [26][27][28]. An increase in ALT or AST levels prior to labour might be due to contractions of the uterine muscles [29].…”
Section: Discussionsupporting
confidence: 93%
“…A significant decrease in serum GGT activity was also found in late pregnancy compared with early pregnancy in women with morning sickness. 18 Our study showed that on change in prothrombin time from first trimester to third trimester of normal pregnancy, there was no significant change between the two trimesters. In a study by Olorunshola et al, the result of PT showed no statistically significant difference in the first and third trimesters except in the second trimester.…”
Section: Discussionmentioning
confidence: 49%